How Toxic Bosses and Poor Leadership Contribute to Employee Depression and Anxiety - Olena Derkach (The American Journal of Management and Economics Innovations, 2025)
The article examines the detrimental impact of toxic management and poor leadership on employee well-being and organizational performance. Unlike demanding but fair managers, toxic leaders actively undermine employee morale and workplace effectiveness. Through authoritarian and destructive behaviors such leaders negatively affect employees' mental health, causing increased anxiety and depression. In contrast, toxic leaders create a detrimental environment by actively undermining workplace conditions and employee well-being. Poor leadership, characterized more subtly by passivity, indecisiveness, and inadequate feedback, further exacerbates these problems. Passive leaders frequently avoid conflict resolution and decision-making, resulting in confusion and instability within the workplace. The absence of constructive feedback additionally impedes employees' ability to develop skills and achieve professional growth. The article proposes solutions for mitigating these negative impacts. Organizations can benefit from adopting practices such as early identification of problematic leadership behaviors through constructive feedback mechanisms, including regular and structured feedback sessions and evaluations. Leadership behavior assessment tools and timely interventions, such as 360-degree feedback, can help identify and address problematic managerial behaviors before they become deeply embedded in organizational culture. Additionally, fostering an open and supportive culture is essential, enabling employees to safely express their concerns, thus promoting workplace well-being. The article emphasizes the importance of proactive organizational measures to recognize and reduce toxic leadership behaviors, thereby safeguarding employee mental health and enhancing overall organizational effectiveness. This study will benefit managers, HR professionals, researchers, business owners, and anyone involved in organizational management and employee welfare.